In situ chemical immobilisation by limestone filler of potentially harmful metal(loid) in contaminated soils: Monitoring by Raman spectroscopy. (December 2019) - Pérez-Sirvent, C.; Martínez-Sánchez, M.J.; Veiga, J.M.; Bech, J.; García-Lorenzo, M.L.
Abstract: Mining-contaminated surface waters and acid mine drainage frequently contain high levels of potentially harmful metal(oid)s, some of which are especially relevant because of their toxicity- As, Pb, Cd and, to a lesser extent, Cu and Zn. Limestone filler is used to immobilise these elements taking advantage of its high carbonate content and lower cost. Metal(oid)s are immobilised through precipitation and adsorption in the filler, as confirmed by theoretical calculations and experimental data. The results obtained concerning the concentrations of the elements studied show that they are retained by the filler in concentrations below than those established by the European directive 2008/108/EC. Analyses of the filler were carried out by X-ray diffraction and Raman spectroscopy, and the latter technique was seen to be particularly useful for qualitatively monitoring the processes that take place and for assessing the state of the filler. Highlights: Waters contaminated by potentially toxic elements, are used to mimic acid mine drainage leachates. Limestone fillers used for remediating metal(loid)s contaminated soils are reviewed. Factors affecting limestone- metal(loid)s interaction are discussed. Raman spectroscopy is used as a diagnostic tool for monitoring element trace sorption by limestone filler.